International cooperation of the City of Skopje: Projects for accelerating smart city developments - Branko DIMESKI; Memet MEMETI; Mimoza BOGDANOSKA - JOVANOVSKA (Smart Cities and Regional Development Journal)
During the 21st century, we are witnessing a very dynamic international activity of the cities around the globe. The effect of globalization accelerates the overall processes of international cooperation between the cities and the scope of network development between the cities it goes behind the limits. In this highly dynamic and growing environment, the City of Skopje especially in recent years is very active in the field of international cooperation with other cities in many aspects of societal life while promoting the concept of smart city development. Thus, the main objectives of the paper are directed towards examining the scope of international cooperation of the City of Skopje in the light of numerous international projects for strengthening the cities performances and improving the lives of the city residents. Regarding the scope of the research, the paper mainly builds on the research that already exists in the literature as well as various reports and experiences that were noted in the past. Consequently, the methods of observation and content analysis of the international project cooperation of the City of Skopje as a case study are considered. The research results point to very intensive international smart city cooperation of the City of Skopje with many cities around the globe in many aspects of the human life. The results of the research can serve as a great source of very important data on smart city concept of the City of Skopje for both academicians and researchers i.e. practitioners. The research in the paper impose a great value for any other same or similar research in the future by concluding that the City of Skopje is very active in promoting the concept of smart city development in the field of energy, transportation, pollution and air quality, local economic development etc.